Isolation and identification of Lactococcu lactis producing nisin - ZHOU Xu-xia; YAO Jiang-tao; LI Wei-fen (浙江大学学报. 农业与生命科学版)
In Lactococcus lactis strains producing nisin, nisin production is encoded by a large conjugative nisin-sucrose transposon including genes involved in immunity to nisin, and under the guidance of this principle, 6 strains were isolated from fresh milk samples on M17 culture medium supplemented with nisin, sucrose and bromocresol. Further analysis of physiological and biochemical characteristics, 16S rDNA nucleotide sequences of these strains and test for antimicrobial activities of their fermentation products revealed that, two nisin-producing strains and two strains that were resistant to but failed to produce nisin were obtained.